Gendered ageism and gray hair: must older women choose between feeling authentic and looking competent?. (4th March 2022) - Cecil, Vanessa; Pendry, Louise F.; Salvatore, Jessica; Mycroft, Hazel; Kurz, Tim
ABSTRACT: Aging women frequently use hair dye to disguise their age in order to avoid being stigmatized as "old". Recently, however, some have chosen naturally gray hair. Informed by Goffman's theory of stigma, we investigated why they would do so in the face of age-discrimination, and their experiences of the process. We identified two major, oppositional themes, competence and authenticity . Despite wanting to avoid perceptions of old-thus-incompetent, women risked gray hair in order to feel authentic. However, they employed other beauty practices to mitigate the effects of gray hair, indicating conflict between a (subjectively) authentic appearance and societal perceptions of competence.